Systemic approaches to early interventions in a community affected by organized violence - Ajduković, Dean (Array, 2003)
Wars are an extreme form of organised massive violence that have a profound impact on the community, the family and at an individual level. Human-made disasters, especially those that are characterised by high levels of long-lasting stress are socially disruptive and weaken the capacity to provide support. This contrasts with single though major events like natural disasters when communities are typically brought closer together. Three groups of factors have been recognised as key determinants of social and psychological consequences of traumatic events: characteristics of the events and context in which they take place, characteristics of individuals affected and their personal histories, and characteristics of the prevailing social situation. Just as massive trauma exposure occurs within a given community social context, so it is the very same but altered context that is essential for healing processes to occur. The importance of mobilizing social, community and family networks in support of survival care is essential. The systemic community-based concept of early interventions is embedded in the framework of empowerment of individual clients, families and whole communities. The core principle for this approach after trauma is that it presumes a measure of resilience and coping in service users and their networks. It also looks for salutogenic effects that arise from such interventions that may be conducive to longer term post-traumatic growth of individuals and communities. This can occur not only at the level of symptoms of maladjustment after trauma exposure but also at the level of re-establishing basic social structures and strengthening community coherence.